Desain Pembelajaran Materi Permutasi untuk Mengoptimalkan kemampuan Berpikir Kombinatorial Mahasiswa Program Studi Pendidikan Matematika - Ihsan, Iden Rainal; Kosasih, Usep (xxxx-xxxx)
The background of this research is the difficulties experienced by students in comprehending comprehensively and and solving problems related to the concept of permutation. Researchers also consider the importance of combinatorial thinking skills of students which in this case need to be optimized. This study aims to make learning design permutation material that can optimize students combinatorial thinking skills. This research was conducted at the place where the author worked in combinatorics and graph classes even semester 2017-2018 school year with 12 participants. This research is a research design consisting of 3 stages. The first stage is preliminary research, researcher analyzes the needs and context of learning activities, studies of literature, and develops a framework of thinking. The second stage is the stage of development, researcher validates the learning design for further revision (improvement), application design in class, and improvement based on meetings. The third stage is the assessment stage, researcher provides evaluation questions to students to find out the results of the application of the design related to the optimization of combinatorial thinking skills. The design results obtained in general are up to set review activities, discussion, self reflection, and evaluation. The second result is that there are 9 students (75%) who master all stages of combinatorial thinking.